The Impact of Agricultural Insurance on Total Factor Productivity in Agriculture - Xiong, Hao; Song, Wenqian (Journal of Theory and Practice in Economics and Management, 2025)
Improving total factor productivity (TFP) in agriculture is essential for advancing agricultural modernization and ensuring food security. This study utilizes panel data from 30 Chinese provinces spanning 2011 to 2021 and employs a two-way fixed effects model to investigate the impact of agricultural insurance depth on agricultural TFP. A mediation model is further introduced to examine the intermediary role of agricultural mechanization within this relationship. The empirical results indicate that agricultural insurance significantly enhances TFP, with agricultural mechanization serving as a partial mediator. Moreover, regional heterogeneity is evident: the impact of agricultural insurance is more pronounced in the central and western regions, while the eastern region also shows a positive but comparatively moderate effect. This study underscores the mechanism linking insurance, mechanization, and TFP, offering empirical support for regionally differentiated agricultural insurance policies. The findings highlight the importance of refining insurance product design, promoting mechanization, and integrating insurance with agricultural risk management to enhance production efficiency.